HGG-04. PERICYTE-DERIVED PERIOSTIN IS CRUCIAL FOR NEO-VESSEL FORMATION IN GLIOMA. Issue 2 (22nd June 2018) - Zhu, Changbin; Chrifi, Ihsan; Zhao, Yang; Kros, Johan; Cheng, Caroline; Ma, Jie
Abstract: Glioblastoma, as the most malignant type, is characterized by robust angiogenesis. In previous study, periostin is one of the highest enriched extracellular matrix components. The latest study pointed that the origin of periostin was glioma initiating cell and associated with glioma progression and prognosis. While, the continuous staining pattern of periostin in tissues which indicated a pericyte-like phenotype did not go parallel with the glioma initiating cell origin. We aim to confirm pericyte is the major source of periostin as well as its functions in pericyte in the angiogenesis of glioblastoma. To this aim, with the support of TCGA and CGGA database, immunostaining and western blot was used to define periostin expressing cells. Further, knocking down periostin in pericyte was followed by 3D-tube formation assay, migration assay to assess the POSTN-mediated pericyte function. Periostin expressing cells majorly displayed the phenotype of mural cells with co-expression of PDGFRB, a well-known pericyte marker. Cells with periostin knockdown displayed a diminished vascular formation when co-cultured with endothelial cells in 3D-tube formation assay. Mechanistically, pericyte with periostin knockdown expressed lower abundance of pro-angiogenic factors mainly via the PDGFB-PDGFRB axis and further affected the activation of intracellular JNK pathway. In addition, the migration of pericyte was attenuated by periostin knockdown mainly via the aberrant modulation of focal adhesion kinase together with the insufficient expression of vinculin. Periositn, as expressed by pericyte, is essential in mediating glioma angiogenesis through various molecular mechanisms. Targeting periostin or its related pathways would be valuable in developing novel therapeutic regimens for GBM patients.